Speech Recognition for English Sentences with Malay Accent - Keumala Anggraini; Van FC, Lucky Lhaura; Darmayunata, Yuvi (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2022)
Some countries conduct speech research using accents. One language that has a different accent is English. English is an international language that is often used to communicate with citizens of other countries. For beginner, many difficulty to translate English with accent, include malay accent. This study performs speech recognition using English and Riau Malay accents. This research use Google Recognizer to cut words in sentences, Mel Frequency Cepstral Coefficient for feature extraction, and Hidden Markov Model for classification. The accuracy of this research is 94.02%.